Financial Performance Evaluation Based on Economic Value-Added at PT XYY (Persero) Tbk - Sudarsono Sudarsono; Adhi Surya Harahap (Journal of Social Science, 2023)
ROA and ROE PT XYZ has fluctuated, but the two financial ratios do not give a clear picture of the company's ability to generate earnings or profits for shareholders or potential investors. The purpose of this research is to find the value added to the financial performance of XYZ by using EVA, and formulate policies and management strategies in accordance with the conditions XYZ EVA value. EVA value obtained by considering the value of NOPAT, WACC and Invested Capital. This type of research is historical research, the analysis of the data used is descriptive statistical analysis. EVA calculation results for 5 (five) years has a value> 0 indicates a positive value, it means a process of value-added, or the company is able to generate the level of return that exceeds the cost of capital operation.